PENGAWASAN PROYEK PEMBANGUNAN PAGAR PEMAKAMAN UMUM DI DESA LIMAU MANIS KECAMATAN KAMPAR KABUPATEN KAMPAR - Rizky, Muhammad; Sadad, Abdul (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
The purpose of this study was to determine the supervision of the control of contract implementation, supervision of the physical implementation of construction, and orderly supervision of financial administration. The problem in this research is the lack of supervision related to the construction of a public cemetery fence funded by the Kampar district budget, and the quality of the TPU fence in Limau Manis Village is less than optimal. This can be seen based on the length that is considered less than the maximum because the fence does not cover the entire burial area, not to mention the problem of cracks in the wall that may be caused by a building foundation that is not optimal. This type of research is descriptive qualitative with a qualitative approach that aims to provide a systematic description of the ongoing situation on the object of research. The location of the study was conducted in Limau Manis Village, Kampar Regency.Based on the results of the research analysis, it can be concluded the research concludes that the Supervision of Public Cemetery Fence Construction project in Limau Manis village, Kampar District, Kampar Regency consists of aspects of supervision of work environment, time, cost and quality of construction. From the aspect of the scope of work carried out in particular relating to the Project Management Organization, Field Submission, Contract Implementation Preparation Meeting (PCM), and the implementation methods and work methods. This was also demonstrated by the project signpost obtained in the field. Aspect of Time with a predetermined target date or completion date that is 50 working days. The cost aspect is known that the construction of the TPU fence in Limau Manis Village is a grant from the Kampar district funded by the Kampar Regency APBDP in 2019 which is listed as a Rp.120,398,000 figure. From the quality aspect by checking the quality of work completion, both in quantity and quality. If there are still shortcomings and do not meet the requirements, then the service provider must repair and complete them first to be submitted again.